Complementary High Spatial Resolution Methods in Materials Science and Engineering2 . Issue 4 (31st January 2017) - Paris, Oskar; Lang, David; Li, Jiehua; Schumacher, Peter; Deluca, Marco; Daniel, Rostislav; Tkadletz, Michael; Schalk, Nina; Mitterer, Christian; Todt, Juraj; Keckes, Jozef; Zhang, Zaoli; et al.
Abstract : This review features the potential of modern high spatial resolution methods in materials science and engineering by presenting a selection of scientific examples covering bulk materials, as well as hard coatings, semiconductors, and mesoporous thin films. Complementary techniques are employed to study microstructure and/or texture and stresses in multiphase Mo‐, Al‐, and Mg‐base alloys, in several nitride‐ and boride‐based hard coatings, in silicon, as well as in mesoporous silica films. Although far from being comprehensive, the chosen examples aim at underlining the importance of modern electron microscopy based methods and of scattering/diffraction techniques at large scale neutron and synchrotron radiation facilities for modern materials research. In addition, atom probe tomography, Raman scattering and atomic force microscopy are also highlighted. Abstract : The potential of modern high spatial resolution methods in materials science and engineering is demonstrated. Scientific examples include characterization of precipitates in multiphase alloys, as well as determination of stresses in coatings and mesoporous thin films, underlining the importance of modern electron microscopy techniques and of scattering/diffraction at large scale facilities. Moreover, atom probe tomography, Raman scattering and atomic force microscopy are also highlighted.